A RASCH MODEL MEASUREMENT ANALYSIS ON SCIENCE LITERACY TEST OF INDONESIAN STUDENTS: SMART WAY TO IMPROVE THE LEARNING ASSESSMENT - Rosita Uli Sihombing; Dali S. Naga; Wardani Rahayu (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
Report of a test assessment is usually carried out separately between the level of difficulty of the test items and the student’s ability. In addition, the analysis of test results is sometimes not clearly presented in a complete and in-depth explanation. This study aimed to explain the assessment process on the instrument of Science Literacy Test for Indonesian Students (SLTIS) conducted by 94 students from the 9th grade of junior high school. Those were 41 students from private schools and 53 from public schools. There were 36 test items with four possible answers for each item. In details, the findings were reported as follows: the item reliability was very good; two items were indicated to have different item functioning (DIF), and the data were fit to the model; public school students were slightly better than private school students, and there was no difference in achievement between male and female students. SLTIS instrument was suitable for diagnostic test and had a high information value on the students with moderate ability. The current study presented a smart way on how to apply the objective measurement to improve the education assessment. Keywords: science literacy, indonesian schools, Science Literacy Test for Indonesian Students (SLTIS), Rasch Measurement Model (RMM)